2021
DOI: 10.1002/adfm.202110881
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Oxide Material for Self‐Targeting and Automatic‐Degrading Photothermal Tumor Therapy in the NIR‐II Bio‐Window

Abstract: Developing photothermal agents (PTAs) for tumor therapy has three prerequisites: selectively targeting tumors, efficiently converting near-infrared (NIR) photoenergy to heat, and degrading after the cure. These make up a combination rarely found in one material. Here a metal-acid treatment is reported to hydrogenate metal oxide, bestowing the produced H x MoO 3 with metal-like electronic structure which enables harvesting NIR-II light (1000−1350 nm wavelength). Importantly, created by putting acid protons into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…[30] PTT, as a new tumor treatment method with simple operation procedures, strong spatiotemporal selectivity, high therapeutic specificity, good tumor inhibition effect, and no damage to the surrounding healthy tissue, is playing an increasingly important role in tumor treatment. [31] PTT can absorb near-infrared (NIR) light including NIR-I (700-900 nm) and NIR-II (1000-1700 nm), which gets converted into heat energy to kill tumor cells using photothermal agents (PTAs). [32] Liu et al designed PEGylated Mn-based SAzymes using a coordination strategy between Mn 2+ and N atoms in hollow ZIF-8 frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…[30] PTT, as a new tumor treatment method with simple operation procedures, strong spatiotemporal selectivity, high therapeutic specificity, good tumor inhibition effect, and no damage to the surrounding healthy tissue, is playing an increasingly important role in tumor treatment. [31] PTT can absorb near-infrared (NIR) light including NIR-I (700-900 nm) and NIR-II (1000-1700 nm), which gets converted into heat energy to kill tumor cells using photothermal agents (PTAs). [32] Liu et al designed PEGylated Mn-based SAzymes using a coordination strategy between Mn 2+ and N atoms in hollow ZIF-8 frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The Mo 3d signals present a similar change on the MoN/Al 2 O 3 (0001) surface in CO 2 + H 2 as MoN/Au (Figure S11). All XPS results in combination with Raman data confirm that hydrogenated molybdenum oxide layers form on the MoN catalyst in CO 2 + H 2 …”
Section: Resultsmentioning
confidence: 55%
“…Recently, the low cytotoxicity and good biocompatibility of Mo-NMs, especially molybdenum oxides have been proved by preliminary biosafety evaluation due to their biodegradability. [68,107,170,224,225] For example, Yu et al reported that the Fe-doped MoO x nanoparticles displayed excellent biocompatibility, which was demonstrated by the normal blood biochemical indices and organ histological analysis of mice treated by Fe-MoO x at different time intervals. No obvious toxicity and other adverse effects at certain time (2 weeks) were found, suggesting the excellent biosafety of Fe-MoO x nanoparticles (Figure 12A).…”
Section: Biosafety Of Mo-nmsmentioning
confidence: 99%